Organic Solar Cells: Water Ingress in Encapsulated Inverted Organic Solar Cells: Correlating Infrared Imaging and Photovoltaic Performance (Adv. Energy Mater. 20/2015). Issue 20 (October 2015) - Adams, Jens; Salvador, Michael; Lucera, Luca; Langner, Stefan; Spyropoulos, George D.; Fecher, Frank W.; Voigt, Monika M.; Dowland, Simon A.; Osvet, Andres; Egelhaaf, Hans‐Joachim; Brabec, Christoph J.
<x xml:space="preserve">Abstract</x> Water ingress represents one of the major reliability concerns for the fabrication, storage, and operation of organic photovoltaic devices. In article number 1501065, Jens Adams and co‐workers track water‐induced photovoltaic degradation in organic solar cells using full frame thermographic and electroluminescence imaging and present a diffusion model for predicting the propagation of water in encapsulated devices. Cover design by George Spyropoulos.